2021
DOI: 10.3389/fphar.2021.765563
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomics and Network Pharmacology to Establish the Action Mechanism of Qingrekasen Granule for Treating Nephrotic Syndrome

Abstract: Nephrotic syndrome (NS) is a clinical syndrome resulting from abnormal glomerular permeability, mainly manifesting as edema and proteinuria. Qingrekasen granule (QRKSG), a Chinese Uyghur folk medicine, is a single-flavor preparation made from chicory (Cichorium intybus L.), widely used in treating dysuria and edema. Chicory, the main component in QRKSG, effectively treats edema and protects kidneys. However, the active components in QRKSG and its underlying mechanism for treating NS remain unclear. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 69 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…It is commonly seen clinically in the treatment of hepatitis, nephritis, gastric fever, hyperlipidemia, hyperuric acid, gout and various febrile diseases. 11 Its health care products and preparations are in various forms, such as granules, oral liquid, pills, and capsules. So far, Cichorium glandulosum Boiss.…”
Section: Application In Traditional Chinese Medicine and Dietmentioning
confidence: 99%
“…It is commonly seen clinically in the treatment of hepatitis, nephritis, gastric fever, hyperlipidemia, hyperuric acid, gout and various febrile diseases. 11 Its health care products and preparations are in various forms, such as granules, oral liquid, pills, and capsules. So far, Cichorium glandulosum Boiss.…”
Section: Application In Traditional Chinese Medicine and Dietmentioning
confidence: 99%
“…In this study, serum samples were thawed at room temperature, eluted with 600 μL methanol, and incubated in an ice bath for 15 , following established GC/MS research protocols (Duan et al, 2021). The tube was then centrifuged for 10 min and the supernatant was concentrated via centrifugation before being evaporated to dryness.…”
Section: Pretreatment Of Serum Samplesmentioning
confidence: 99%
“…Varghese and Majumdar proposed network pharmacology as an initial inherent approach in identifying the repurposing and synergism of drug candidates for NS treatment [ 11 ]. Some previous studies have identified the efficacy and underlying mechanisms of TCMs treating NS via network pharmacology [ 12 , 13 ]. For instance, Yiqi Huoxue Decoction has been found to enhance renal function and alleviate podocyte injury in NS, and the potential mechanisms involved PI3K-AKT and NF- κ B pathways based on network pharmacology [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Yiqi Huoxue Decoction has been found to enhance renal function and alleviate podocyte injury in NS, and the potential mechanisms involved PI3K-AKT and NF- κ B pathways based on network pharmacology [ 12 ]. Duan et al established the underlying mechanism of Qingrekasen granule against NS, including promoting autophagy and antiapoptosis through regulating the expression of AKT1, CASP3, BCL2L1, and mTOR to protect podocytes and maintain renal tubular function [ 13 ]. Furthermore, Zhang et al revealed that FHD possesses the antinephrotic syndrome effect in rat nephropathy model; however, the relative underlying mechanisms have not been fully elucidated [ 14 ].…”
Section: Introductionmentioning
confidence: 99%